The biology, ecology and management of the larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae). (December 2021) - Quellhorst, Hannah; Athanassiou, Christos G.; Zhu, Kun Yan; Morrison, William R.
Abstract: The invasive larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae), originating from Meso-America, is a devastating stored product pest of maize ( Zea mays L.) and cassava ( Manihot esculenta ). This species can destroy up to 40% of stored maize within four months. Despite four decades of research, P. truncatus has spread throughout Africa, while decimating maize and cassava production. Given the continuing problems with P. truncatus, the likelihood for its continued range expansion under climate change, and its status as a species of concern in many countries, the objective of this review was to provide an updated and comprehensive freely accessible record of the distribution and spread, biology, development, and ecology, host preferences, chemical ecology, detection, and monitoring, and management of P. truncatus . We conducted a search of the literature from 1911 to 2021 using Google Scholar and Web of Science to find all papers related to key search terms. We found that P. truncatus has been recorded in 36 countries across the globe, including 21 now in Africa. A recent predictive model found that the insect has been limited to tropical and subtropical regions but could likely spread to temperate regions as temperatures rise with climate change. Conspecifics respond to their two component, male-produced aggregation pheromone early after eclosion, but quickly switch to other cues as older adults. At close-range, P. truncatus may use food cues, but host volatiles are not involved in long-range host finding of commodities. Research on managing P. truncatus has mostly focused on chemical control to the detriment of other tactics, with the most promising tactic likely to be the different hermetic storage technologies. Many outstanding areas of basic behavior and ecology remain to be assessed for P. truncatus . We highlight specific areas that should be prioritized for further work in order to better manage and reduce the impact of this invasive insect pest. Graphical abstract: Image 1 Highlights: We conducted a search of the literature from 1911 to 2021 using Google Scholar and Web of Science on P. truncatus . We found that P. truncatus has been recorded in 36 countries across the globe, including 21 now in Africa, with spread continuing. We synthesize basic biology, development, chemical ecology, competition, and life history of P. truncatus . Managing P. truncatus has focused on chemical control to the detriment of other tactics, with the most promising tactic likely to be novel hermetic technologies.